1959
DOI: 10.1152/jappl.1959.14.6.1018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food deprivation on treadmill running in dogs

Abstract: Effect of food deprivation on endurance capacity was studied in dogs under the following conditions: a) 3 and 5 days of fasting with daily high levels of energy expenditure and b) 15 days of fasting with low daily levels of energy expenditure. Relative maximum performance, i.e. endurance capacity under conditions wherein work dehydration is a limiting factor, is unaffected by 10–15% body-weight loss and hypoglycemia induced by acute food deprivation. Even with weight loss up to 22%, capacity for daily moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
2

Year Published

1965
1965
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
3
2
2
Order By: Relevance
“…A decrease in blood glucose concentrations detected in well-fed Beagles during endurance exercise was not evident in food-deprived Beagles, which suggested that delivery of glucose to muscle matched the demand in food-deprived but not well-fed dogs. 4 However, in the Greyhounds evaluated in the present study, serum glucose concentrations increased after a 30-second race, compared with the values before the race, and serum glucose concentrations after racing were unaffected by restricted access to food. Increasing body temperature has also been observed to limit performance in exercising dogs, 4,21 but the increase in rectal temperatures during a race was unaffected by food deprivation in these Greyhounds.…”
Section: Restricted Food Intakecontrasting
confidence: 59%
See 1 more Smart Citation
“…A decrease in blood glucose concentrations detected in well-fed Beagles during endurance exercise was not evident in food-deprived Beagles, which suggested that delivery of glucose to muscle matched the demand in food-deprived but not well-fed dogs. 4 However, in the Greyhounds evaluated in the present study, serum glucose concentrations increased after a 30-second race, compared with the values before the race, and serum glucose concentrations after racing were unaffected by restricted access to food. Increasing body temperature has also been observed to limit performance in exercising dogs, 4,21 but the increase in rectal temperatures during a race was unaffected by food deprivation in these Greyhounds.…”
Section: Restricted Food Intakecontrasting
confidence: 59%
“…Beagles running on a treadmill at 6 km/h consumed less energy as they lost weight during 15 days of food deprivation, even when work load was adjusted for weight. 4 If this relationship applies to Greyhounds during a sprint, then less energy would be required by lightweight dogs than heavier dogs to complete a race. Furthermore, Greyhounds mostly rely on anaerobic and aerobic metabolism of carbohydrates during a 30-second race.…”
Section: Restricted Food Intakementioning
confidence: 99%
“…They confirmed these reports when they demonstrated that short-term exercise caused an increase in glucocorticoids, while prolonged exercise caused a decrease. Many other workers have obtained similar results (Masson, 1941;Haldi and Wynn, 1946;Young, 1959;Stolyarova, 1968;and Chin and Evonuk, 1971). It has been suggested that adrenal steroid levels remain constant in aging (Grad et al, 1967eund Friedmsm et al, 1969.…”
Section: Adrenocortical Influencessupporting
confidence: 56%
“…Ingbar and Freinkel (1955) have reported that long term exercise decreased indices of cortical activity, namely plasma corticoid levels. Similar results have been obtained by Young (1959), Viru and Akke (1969) and Chin and Evonuk (1971).…”
Section: Thyroid-adrenal Cortical Interactionssupporting
confidence: 90%
“…This latter finding is not consistent with the reports of others that prolonged exercise decreases corticosteroidogenesis (Chin and Evonuk, 1971;Craig, 1972;Young, 1959). It is of interest to note that previous interpretation of the level of cortical function was based for the most part upon plasma levels of corticosteroids and not upon the actual output of the gland.…”
Section: Exercise Effects and Exercise-acth Interactioncontrasting
confidence: 81%